2022
DOI: 10.1515/secm-2022-0017
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of behavior and ultimate strength of composite column

Abstract: Composite sections are found to be a novel technique in modern day scenario of construction. This stands tall than the ordinary and conventional type of constructions. Columns as a structural element play a vital role in structural frame. This research comments on the behavior of composite columns. The main objective of this study is to analyze the behavior of steel-encased concrete composite columns as experimentally under axial compression and the mode of failure under ultimate failure and yield point. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The strength, ductility, and stiffness of columns with these types of reinforcement were enhanced. Ayyasamy et al [13] investigated empirically and numerically the performance of composite columns encased by steel. The investigation results revealed that the composite column encased by steel had more strength than the conventional RC column and I-steel column.…”
Section: Introductionmentioning
confidence: 99%
“…The strength, ductility, and stiffness of columns with these types of reinforcement were enhanced. Ayyasamy et al [13] investigated empirically and numerically the performance of composite columns encased by steel. The investigation results revealed that the composite column encased by steel had more strength than the conventional RC column and I-steel column.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the elements of the load-bearing body under the design earthquake ensure minor and repairable damages [32]- [38]. Furthermore, they minimize the damages for earthquakes of lower intensity and with a higher probability of occurrence, when imposing the "design" seismic actions with an acceptably small probability of exceeding them during the life of the structure [39], [40]. With the flexural yielding of critical areas, i.e., the formation of plastic joints, the load-bearing body is able to turn into an elastoplastic mechanism, which continues to respond to the peaks of seismic movements with prac-tically constant intensity, releasing in each cycle a significant part of the seismic energy it has absorbed [20], [32], [34], [41]- [44].…”
Section: Introductionmentioning
confidence: 99%